The September 2020 Wildfires over the Pacific Northwest - Mass, Clifford F.; Ovens, David; Conrick, Robert; Saltenberger, John (Weather and forecasting, 2021)
A series of major fires spread across eastern Washington and western Oregon starting on 7 September 2020, driven by strong easterly and northeasterly winds gusting to ~70 kt (1 kt ≈ 0.51 m s −1 ) at exposed locations. This event was associated with a high-amplitude upper-level ridge over the eastern Pacific and a mobile trough that moved southward on its eastern flank. The synoptic environment during the event was highly unusual, with the easterly 925-hPa wind speeds at Salem, Oregon, being unprecedented for the August–September period. The September 2020 wildfires produced dense smoke that initially moved westward over the Willamette Valley and eventually covered the region. As a result, air quality rapidly degraded to hazardous levels, representing the worst air quality period of recent decades. High-resolution numerical simulations using the WRF Model indicated the importance of a high-amplitude mountain wave in producing strong easterly winds over western Oregon. The dead fuel moisture levels over eastern Washington before the fires were typical for that time of the year. Along the western slopes of the Oregon Cascades, where the fuels largely comprise a dense conifer forest with understory vegetation, fire weather indices were lower (moister) than normal during the early part of the summer, but transitioned to above-normal (drier) values during August, with a spike to record values in early September coincident with the strong easterly winds. Forecast guidance was highly accurate for both the Washington and Oregon wildfire events. Analyses of climatological data and fuel indices did not suggest that unusual preexisting climatic conditions were major drivers of the September 2020 Northwest wildfires.